Sarcoglycans are enriched at the neuromuscular junction in a nerve-dependent manner - Michela Gloriani; Bianca Cheli; Chiara D’Ercole; Veronica Ruggieri; Marianna Cosentino; Mireia Serrat Pineda; Biliana Lozanoska-Ochser; Francesca Grassi; Marina Bouché; Luca Madaro; Carles Sánchez Riera (Cell Death and Disease)
Abstract Sarcoglycanopathies are heterogeneous proximo-distal diseases presenting severe muscle alterations. Although there are 6 different sarcoglycan isoforms, sarcoglycanopathies are caused exclusively by mutations in genes coding for one of the four sarcoglycan transmembrane proteins (alpha, beta, gamma and delta) forming the sarcoglycan complex (SGC) in skeletal and cardiac muscle. Little is known about the different roles of the SGC beyond the dystrophin glycoprotein complex (DGC) structural role. Here, we show that SGC proteins are enriched at the post-synaptic membrane of neuromuscular junctions (NMJs). Using a mouse model lacking the beta-sarcoglycan subunit, we describe for the first time that the loss of the SGC in the NMJ area results in alterations of pre- and postsynaptic membrane, as well as a significant reduction of membrane potential. Moreover, using different denervated wild-type mouse models, we demonstrate that nerve presence precedes the sarcoglycan enrichment at NMJ, suggesting a nerve-dependent sarcoglycan expression. Altogether, our findings suggest that pathological decline should no longer be understood only in terms of sarcolemma damage but also in terms of sarcoglycans’ participation in the NMJ. Henceforth, our work paves the way for the identification of new mechanisms involving sarcoglycans and new approaches for the treatment of sarcoglycanopathies.